PENGEMBANGAN ALAT BANTU MESIN CUTTING BESI DENGAN SISTEM CONVEYOR SLIDING MENGGUNAKAN METODE RULA DAN REBA UNTUK MENGURANGI RISIKO GANGGUAN MUSKOLOSKELETAL - Mirajhusnita, Isradias; Syaefulloh, Syaefulloh; Nurwildani, M. Fajar; Sugiono, Mohammad Cipto; Hariyanto, Hariyanto (Universitas PGRI Semarang, 2023)
This The purpose of this study, to identify complaints of Musculoskeletal Disorders (MSDs) experienced by workers at UD. Andika Aluminum and Welding, these complaints include pain in the upper arm, waist, right forearm, right wrist, and right and left knees. The results of the RULA and REBA scores obtained from the highest cutting activities before the use of work tools currently resulted in a high risk of 76 and 75 and decreased after the development of tools, namely to 40 and 39. Assessment of work posture for cutting with ergofellow software obtained RULA scores and the highest REBA is with a RULA score of 7 7 and a REBA of 12 11, which is included in the category